2019
DOI: 10.1186/s12904-019-0475-9
|View full text |Cite
|
Sign up to set email alerts
|

Completion rate of physician orders for life-sustaining treatment for patients with metastatic or recurrent cancer: a preliminary, cross-sectional study

Abstract: Background“End of life” is a difficult topic of conversation in East Asian cultures, even among patients and doctors who share a good rapport. In 2016, the Hospice, Palliative Care, and Life-Sustaining Treatment Decision-Making Act, which took the form of “Physician Orders for Life-Sustaining Treatment,” was introduced in South Korea. This study was conducted to investigate the completion rate of Physician Orders for Life-Sustaining Treatment in patients with advanced cancer on the active recommendation of phy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…25,58 Our findings also show that patients were willing to initiate advance care planning at a particular time in the future or later in the course of their illness. 25,28,33,35,37,38,50,56 With regard to patients' preferences for documenting their conversations, our findings were varied: while some preferred a written document, 24,31,34,54 others preferred verbal communication with their family, and/or healthcare professionals without drafting or signing a written document. 29,43,44,57…”
Section: Behavioral Beliefsmentioning
confidence: 86%
“…25,58 Our findings also show that patients were willing to initiate advance care planning at a particular time in the future or later in the course of their illness. 25,28,33,35,37,38,50,56 With regard to patients' preferences for documenting their conversations, our findings were varied: while some preferred a written document, 24,31,34,54 others preferred verbal communication with their family, and/or healthcare professionals without drafting or signing a written document. 29,43,44,57…”
Section: Behavioral Beliefsmentioning
confidence: 86%
“…Therefore, the author doubted the real possibility of the universal application of patient autonomy for cancer patients in Korea. After 10 years, another study investigated a similar issue under the current LST law [ 22 ]. Here, 71.3% of the advanced cancer patients were willing to have a conversation related to LST with their physicians.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was similar to the preference analysis of cancer patients toward the selection of LST on legal form No. 13 [ 22 ]. Among the patients who signed the form, only 31.9% wanted to stop chemotherapy, whereas all 72 participants refused CPR and mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on intensive care unit doctors in Asia reported that among the factors that these doctors considered to be important in making LST-related decisions, the needs of the family accounted for 77.9%; it was only surpassed by the factors patient’s intention (84.1%) and long-term quality of life [ 3 ]. It is well-established fact that the physician’s perception of the intention of the family and the preference of the patient may sometimes be different than the patient’s original intention [ 1 , 20 , 21 ]. Personal characteristics or experience of the physician could also influence LST-related decisions, which inherently presents the risk of a decision being made contrary to the patient’s intention [ 11 ].…”
Section: Discussionmentioning
confidence: 99%